Is the Interplay between Epigenetic Markers Related to the Acclimation of Cork Oak Plants to High Temperatures? - Correia, Barbara; Valledor, Luis; Meijón, Mónica; Rodriguez, José Luis; Dias, Maria Celeste; Santos, Conceição; Cañal, Maria Jesus; Rodriguez, Roberto; Pinto, Glória (PLoS ONE, 2013)
Trees necessarily experience changes in temperature, requiring efficient short-term strategies that become crucial in environmental change adaptability. DNA methylation and histone posttranslational modifications have been shown to play a key role in both epigenetic control and plant functional status under stress by controlling the functional state of chromatin and gene expression. Cork oak (Quercus suber L.) is a key stone of the Mediterranean region, growing at temperatures of 45°C. This species was subjected to a cumulative temperature increase from 25°C to 55°C under laboratory conditions in order to test the hypothesis that epigenetic code is related to heat stress tolerance. Electrolyte leakage increased after 35°C, but all plants survived to 55°C. DNA methylation and acetylated histone H3 (AcH3) levels were monitored by HPCE (high performance capillary electrophoresis), MS-RAPD (methylation-sensitive random-amplified polymorphic DNA) and Protein Gel Blot analysis and the spatial distribution of the modifications was assessed using a confocal microscope. DNA methylation analysed by HPCE revealed an increase at 55°C, while MS-RAPD results pointed to dynamic methylation-demethylation patterns over stress. Protein Gel Blot showed the abundance index of AcH3 decreasing from 25°C to 45°C. The immunohistochemical detection of 5-mC (5-methyl-2′-deoxycytidine) and AcH3 came upon the previous results. These results indicate that epigenetic mechanisms such as DNA methylation and histone H3 acetylation have opposite and particular dynamics that can be crucial for the stepwise establishment of this species into such high stress (55°C), allowing its acclimation and survival. This is the first report that assesses epigenetic regulation in order to investigate heat tolerance in forest trees.
The following values have no corresponding Zotero field: publisher: Public Library of Science accession-num: 23326451
Keywords: Acclimatization; Acclimatization: genetics; Acetylation; Blotting; CHROMATIN; CORK oak (citation; Deoxycytidine; Deoxycytidine: analogs & derivatives; Deoxycytidine: metabolism; DNA; DNA methylation; Electrolytes; Electrolytes: metabolism; Epigenesis; Gene expression; Genetic; Genetic Markers; Genome; Heat-Shock Response; Heat-Shock Response: genetics; Histones; Histones: metabolism; Physiological; Physiological: genetics; Plant; Plant Leaves; Plant Leaves: metabolism; Plant: genetics; POST-translational modification; Quercus; Quercus: genetics; Quercus: physiology; Random Amplified Polymorphic DNA Technique; Stress; tags); Temperature; TREES -- Research; Western

Proteomic analysis of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) pollen. - Valero Galván, José; Valledor, Luis; González Fernandez, Raquel; Navarro Cerrillo, Rafael M; Jorrín-Novo, Jesús V (Journal of proteomics, 2012)
This paper presents an analysis of Holm oak pollen proteome, together with an evaluation of the potentiality that a proteomic approach may have in the provenance variability assessment. Proteins were extracted from pollen of four Holm oak provenances, and they were analyzed by gel-based (1- and 2-DE in combination with MALDI-TOF/TOF) and gel-free (nLC-LTQ Orbitrap MS) approaches. A comparison of 1- and 2-DE protein profiles of the four provenances revealed significant differences, both qualitative and quantitative, in abundance (18 bands and 16 spots, respectively). Multivariate statistical analysis carried out on bands and spots clearly showed distinct associations between provenances, which highlight their geographical origins. A total of 100 spots selected from the 402 spots observed on 2-DE gels were identified by MALDI-TOF/TOF. Moreover, a complementary gel-free shotgun approach was performed by nLC-LTQ Orbitrap MS. The identified proteins were classified according to biological processes, and most proteins in both approaches were related to metabolism and defense/stress processes. The nLC-LTQ Orbitrap MS analysis allowed us the identification of proteins belonging to the cell wall and division, transport and translation categories. Besides providing the first reference map of Holm oak pollen, our results confirm previous studies based on morphological observations and acorn proteomic analysis. Moreover, our data support the valuable use of proteomic techniques as phylogenetic tool in plant studies.
Keywords: Electrophoresis, Gel, Two-Dimensional; Electrophoresis, Gel, Two-Dimensional: methods; Electrophoresis, Polyacrylamide Gel; phylogeny; Plant Proteins; Plant Proteins: analysis; pollen; Pollen: chemistry; Proteome; Proteome: analysis; Proteomics; Proteomics: methods; Quercus; Quercus: genetics; Quercus: metabolism; Spain; Spectrometry, Mass, Matrix-Assisted Laser Desorpti; Two-Dimensional Difference Gel Electrophoresis

Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) through acorn protein profile analysis. - Valero Galván, José; Valledor, Luis; Navarro Cerrillo, Rafael M; Gil Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of proteomics, 2011)
Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.), the dominant tree species in the typical Mediterranean forest, have been carried out by using electrophoresis-based proteomic analysis of acorns. Ten populations distributed throughout the Andalusia region have been surveyed. Acorns were sampled from individual trees and proteins extracted from seed flour by using the TCA-acetone precipitation protocol. Extracts were subjected to SDS-PAGE and 2-DE for protein separation, gel images captured, spot or bands quantified, and subjected to statistical analysis (ANOVA, SOM and clustering). Variable bands or spots among populations were subjected to MALDI-TOF/TOF and LC-MS/MS for identification. The protein yield of the used protocol varied among populations, and it was in the 2.92-5.92 mg/g dry weight range. A total of 23 bands were resolved by SDS-PAGE in the 3-35 kDa Mr range, with 8 and 12, out of the total, showing respectively qualitative and quantitative statistically significant differences among populations. Data allowed grouping populations, with groups being correlated according to geographical location and climate conditions, to northern and southern, as well as the discrimination of both mesic and xeric groups. Acorn flour extracts from the most distant populations were analyzed by 2-DE, and 56 differential spots were proposed as markers of variability. Identified proteins were classified into two principal categories; storage and stress/defense protein. Besides providing the first reference map of mature acorn seeds, the use of SDS-PAGE and proteomics in characterizing natural biodiversity in forest trees will be discussed.
Keywords: Acorn proteomics; Chromatography; Electrophoresis; Gene Expression Profiling; Holm oak variability; Liquid; Mass; Matrix-Assisted Laser Desorpti; Plant Proteins; Plant Proteins: metabolism; Polyacrylamide Gel; Quercus; Quercus ilex proteomics; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Spectrometry; Tandem mass spectrometry